1999
DOI: 10.1007/s004390051107
|View full text |Cite
|
Sign up to set email alerts
|

β3-Adrenergic receptor Trp64Arg polymorphism does not predict incident CHD or carotid intima-media thickness in a community-based sample of whites: the ARIC study

Abstract: The beta3-adrenergic receptor (beta3-AR) is expressed in adipose tissue and plays a significant role in controlling energy expenditure through the regulation of lipolysis and thermogenesis. The possible clinical importance of the beta3-AR Trp64Arg polymorphism has prompted us to investigate the association between it and the extent of atherosclerosis and risk of incident coronary heart disease (CHD). The ability of the beta3-AR Trp64Arg polymorphism to predict the extent of atherosclerosis and incident CHD has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…There have been many studies about the relationship between Trp64Arg and obesity in adults. [4][5][6][7][8][9][10][11][12][13] Recently, a meta-analysis of the studies in Japanese adults was reported. 31 According to the report, Trp64Arg was associated with BMI in Japanese adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies about the relationship between Trp64Arg and obesity in adults. [4][5][6][7][8][9][10][11][12][13] Recently, a meta-analysis of the studies in Japanese adults was reported. 31 According to the report, Trp64Arg was associated with BMI in Japanese adults.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other studies have indicated that Trp64Arg is associated with coronary heart disease (CHD). 8 However, several other studies have suggested that Trp64Arg is not associated with obesity, CHD or type 2 DM [9][10][11][12][13] Thus, it is still controversial whether Trp64Arg is associated with these metabolic diseases.…”
mentioning
confidence: 99%
“…Candidate genes that have been examined include apoE, [17][18][19][20] paraoxonase, [21][22][23][24] ACE, 22,[25][26][27] cholesterol ester transfer protein, 28 ␤ 3 -adrenergic receptor, 29 and methylenetetrahydrofolate. 22,30,31 The inconsistency among the results from these The ␤ coefficients represent the change in IMT for a 1-SD increase in the predictor.…”
Section: Discussionmentioning
confidence: 99%
“…After Higashi et al [7] had published their data showing that the frequency of the Trp64Arg variant of the ADRB3 gene polymorphism was higher in 83 Japanese patients with CHD (0.247) versus 107 control subjects (0.145), several efforts have been undertaken to replicate these results in similar or different populations [8][9][10][11][12][13][14][15]. Stangl et al so far have performed the largest study, in a cross-sectional design amongst 992 CHD cases and 988 controls in Germany [11].…”
Section: Cases / Controlsmentioning
confidence: 99%
“…Given the importance of obesity, diabetes mellitus and hypertension in the occurrence of coronary heart disease (CHD), these findings suggest that this polymorphism may confer an increased risk of CHD. In contrast to a first report in a small population on the association of Trp64Arg polymorphism with CHD [7], subsequent studies have shown no association [8][9][10][11][12][13][14][15]. We set out to investigate the relationship of Trp64Arg polymorphism in the ADRB3 gene on the occurrence of acute myocardial infarction (AMI) and CHD in middle-aged Dutch women.…”
mentioning
confidence: 92%